Mycelial Cultivation of 4 Edible Mushrooms from Khao Kra-Dong Volcano Forest Park, Thailand - Saensuk, Tepupsorn; Suntararak, Suteera (Asian Health, Science and Technology Reports, 2018)
The edible mushrooms become one of the world’s most expensive foods and have a global market measured in Thailand. In Thailand, the fruiting body of all occurs once a year during rainy season in June – August. So, the objective of this research was to study the optimal mycelial conditions of 4 edible mushrooms collected from Khao Kra-Dong Volcano Forest Park in Thailand: Russula cyanoxantha, Heimiell retispora, Russula virescens and Boletus colossus. The highest mycelial growth of R. virescens and B. colossus were with potato dextrose agar (PDA), followed by potato dextrose agar with 2% volcanic soil (PDA+2% S). The best structures of R. cyanoxantha and H. retispora used for culturing on medium were cap, stalk and spore, respectively. For R. Virescens and B. colossus, the best structures used for culturing on medium were stalk, cap and spore, respectively. The highest colony diameter of R. Cyanoxantha on PDA+2% S with cap was 68.00+1.00 mm. For H. retispora, the highest colony diameters on PDA+2%S with cap and PDA with stalk were 87.00+1.00 mm. and 67.33+1.53 mm., respectively. For R. virescens and B. colossus, the highest colony diameters on PDA with stalk were 91.33+2.08 mm. and 87.00+1.00 mm., respectively. The optimal temperature and pH value for mycelial growth were at 30 °C with pH 7 after 7 days of incubation.